The stars are dying - Peñaranda, Chloe C. (Peñaranda, Chloe C. Nytefall novel., 2024)
"Astraea is a prisoner of her own mind, the past sliding from her grasp like water. But she knows she must escape the tyrannical king who holds her captive and find her clouded memories once again. This quest leads her to the Libertatem, a succession of trials hosted by the king in which five human lands compete for a cycle of safety from the vampires seeking blood, claiming souls, and savaging after dark. But even winning the Libertatum will not keep Astraea safe from vampires. She's made a bargain with Nyte, the beautiful, deadly vampire who stalks her dreams and haunts her waking hours. He promises to keep her safe, but she knows she cannot trust him, cannot trust his lies, even as she finds herself drawn deeper and deeper into his seductive embrace. Caught between Nyte and her own mysteries, Astraea must decide if winning the Libertatem for her kingdom is worth her life, or if protection--and the answers to her past--really are her strongest desires."--